Identification of Yellow Pigmentation Genes in Brassica rapa ssp. pekinensis Using Br300 Microarray. (31st December 2014) - Jung, Hee-Jeong; Manoharan, Ranjith Kumar; Park, Jong-In; Chung, Mi-Young; Lee, Jeongyeo; Lim, Yong-Pyo; Hur, Yoonkang; Nou, Ill-Sup
Abstract : The yellow color of inner leaves in Chinese cabbage depends on its lutein and carotene content. To identify responsible genes for yellow pigmentation in leaves, the transcriptome profiles of white (Kenshin) and yellow leaves (Wheessen) were examined using the Br300K oligomeric chip in Chinese cabbage. In yellow leaves, genes involved in carotene synthesis ( BrPSY, BrPDS, BrCRTISO, and BrLCYE ), lutein, and zeaxanthin synthesis ( BrCYP97A3 and BrHYDB ) were upregulated, while those associated with carotene degradation ( BrNCED3, BrNCED4, and BrNCED6 ) were downregulated. These expression patterns might support that the content of both lutein and total carotenoid was much higher in the yellow leaves than that in the white leaves. These results indicate that the yellow leaves accumulate high levels of both lutein and β -carotene due to stimulation of synthesis and that the degradation rate is inhibited. A large number of responsible genes as novel genes were specifically expressed in yellow inner leaves, suggesting the possible involvement in pigment synthesis. Finally, we identified three transcription factors ( BrA20/AN1-like, BrBIM1, and BrZFP8 ) that are specifically expressed and confirmed their relatedness in carotenoid synthesis from Arabidopsis plants.